Telaah Framing Debat Capres dalam Perspektif Pemilih Muda (Analisis Persepsi dan Preferensi Pemilih Muda pada Pemilu 2024) - Fithriya, Dwi Nur Laela (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Presidential debates are a vital tool in the democratic process, particularly in providing information to voters and aiding them in making decisions. However, the manner in which presidential debates are conducted can impact their effectiveness. Framing is the process of assigning meaning or explanations to an event or issue. The objective of this research is to examine how young voters perceive presidential debates from their perspective. The study utilizes a qualitative descriptive method involving interviews, observations, and literature review. Findings reveal that young voters tend to view presidential debates based on issues relevant to their lives, such as democracy, education, and employment. Overall, this research indicates that young voters tend to frame presidential debates based on issues pertinent to their lives. Additionally, young voters also tend to assess presidential debates based on the candidates' ability to respond to questions and convey their presented vision and mission. Furthermore, young voters also tend to evaluate presidential debates based on the candidates' ability to fulfill their desires. The results of this research will significantly impact future presidential debates. Presidential debates should align with the information needs of young voters and capture their attention. Key words: presidential debates, framing, young voters, 2024 elections